Ranking of patient and surgeons' perspectives for endpoints in randomized controlled trials: lessons learned from the POVATI trial [ISRCTN 60734227] - Fischer, Lars; Deckert, Andreas; Diener, Markus K.; Zimmermann, Johannes B.; Büchler, Markus W.; Seiler, Christoph (Langenbeck's archives of surgery, 2011)
Surgical trials focus mainly on mortality and morbidity rates, which may be not the most important endpoints from the patient's perspective. Evaluation of expectations and needs of patients enrolled in clinical trials can be analyzed using a procedure called ranking. Within the Postsurgical Pain Outcome of Vertical and Transverse Abdominal Incision randomized trial (POVATI), the perspectives of participating patients and surgeons were assessed as well as the influence of the surgical intervention on patients' needs.